Processo de envelhecimento, velhice e vulnerabilidade no contexto de situação de rua - Oliveira, Tatiane Vieira Martins de (Universidade Federal de São Carlos, 2020)
As the demographic transition becomes a reality, it is of the utmost importance to study the various contexts in which the population is inserted and to influence aging. Currently there are few studies that seek to identify the scenario of elderly people in a vulnerable situation because they do not have a fixed residence. Thus, the objective of this study is to analyze the vulnerability of the population in the street situation, evaluating the relationship between care, reception offered by the equipment and the impacts on health conditions. This is a cross- sectional, descriptive study based on the mixed method of investigation through semi- structured interviews and the application of screening tools widely used in research, the Clinical Functional Vulnerability Index (IVCF-20), Minimal Mental State Examination, as well as subjective assessment of health and overall satisfaction with life. Having as target people aged 45 or over, who use the equipment that serves the homeless population of the city of São Carlos - SP. The sample consisted of 40 individuals with an average age of 51 (± 5.34) years, a greater predominance of men, with a low level of education, and presenting financial demands resulting from chronic unemployment. With an average of approximately 8 (± 8.69) years on the streets. Presenting chemical dependency, and a considerable number of diseases and health complaints. In addition, 25% had cognitive impairment and 35% fragility. They reported low social support. Thus, they present demands for health and social assistance in the aging process.
Aging process, old age and vulnerability in the context of homelessness
Keywords: Envelhecimento; Pessoas em situação de rua; Vulnerabilidade social; Saúde; Aging; Homeless persons; Social vulnerability; Health; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS HUMANAS; OUTROS::CIENCIAS SOCIAIS; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::POLITICA PUBLICA E POPULACAO::POLITICA POPULACIONAL; CIENCIAS SOCIAIS APLICADAS::SERVICO SOCIAL::SERVICO SOCIAL APLICADO::SERVICO SOCIAL DA HABITACAO